Poverty in Rural Cambodia: The Differentiated Impact of Linkages, Inputs and Access to Land - Anders Engvall; Örjan Sjöberg; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2007)
Cambodia has been growing rapidly over the past few years but still remains one of the poorest countries in East Asia. In particular, poverty is widespread in rural Cambodia. This paper examines rural poverty in Cambodia with a view to furthering our understanding of the factors that might explain its occurrence and persistence. Setting out from the existing literature, it appears that reduced rural poverty in Cambodia would have to rest on two pillars. Firstly, improvements in agricultural productivity are necessary. Secondly, other income earning opportunities for the rural population have to be established. Using the 2004 Cambodian Socio-Economic Survey, and focusing on the binding constraints to development and poverty alleviation, we add detail to this picture. Our econometric results show that the main causes to poverty differ between landowners and landless and between different regions. Inputs to agriculture are critical to the landowning poor whereas linkages with the rest of the economy, while also essential to landowners, are of vital importance to the landless poor if their lot is to be improved.
Keywords: O12; O13; O18; 330; Asia; Cambodia; Poverty; Rural; Agriculture; Linkages; Ländlicher Raum; Landwirtschaft; Armut; Kambodscha